Office processes in local government units on the example of the Municipal Office in Nowa Sól (Discourse of Law and Administration, 2025)
The article touches on the problems that government officials face every day. Every day, the office receives and registers several hundred letters in a traditional way and with use of electronic systems. This correspondence is from both individuals and legal entities. The aim of the article is to analyze the literature on the subject and to examine the opinions of the employees of the  Municipal Office in Nowa Sól regarding both systems. The research method was a diagnostic survey, the technique was a survey, and the tool was a questionnaire, which was answered by 60 respondents. The results of the research shows that the employees of the Municipal Office consider the electronic system to be more effective in comparison to the traditional system.
Keywords: office processes; traditional system; electronic system; incoming correspondence; outgoing correspondence